Impact of Mobile Internet Application on Farmers’ Adoption and Development of Green Technology - Huang, Zhenzhen; Zhuang, Jiayu; Xiao, Shuo (Sustainability, 2022)
Mobile Internet refers to a new mode of information interaction through mobile terminals and the use of wireless communication to access information services. The mobile Internet has provided a new model for the traditional information circulation mode, rural economic structure, and social transformation. With an association between the mobile Internet and farmers’ adoption behavior of new green technology, this paper investigated the impact of mobile Internet application on farmers’ adoption of green technology through a mediating effect model. From the perspective of new agricultural technology diffusion and based on the perspective of factor substitution, we decompose the mechanism that mobile Internet applications affect the adoption of new wheat varieties. Along the path of information transmission, evaluation, and adoption of new wheat varieties, we deeply explored the impact of the mobile Internet on the adoption of new wheat varieties by different types of wheat growers. The results show that there is a significant mediating effect of information acquisition ability, risk attitude, and expected return on the influence of the mobile Internet on green technology adoption. For the adoption mechanism of new green varieties, there was a distinct difference among various farmers.